Synergistic activity between Triphala and selected antibiotics against drug resistant clinical isolates - Amirthasingam Manoraj; Vasanthi Thevanesam; B. M. R. Bandara; Asela Ekanayake; Veranja Liyanapathirana (BMC, 2019)
Abstract Background Triphala is an indigenous medical product used for a variety of diseases. This study was conducted to determine the effect of Triphala on antibiotic properties of gentamicin and oxacillin against multi-drug resistant organisms. Methods The checkerboard method was used to determine the synergy of Triphala with gentamicin and oxacillin against multi-drug resistant (MDR) Gram negative bacilli and methicillin-resistant Staphylococcus aureus (MRSA) using 2,3,5-triphenyltetrazolium chloride (TTC) assay. Fractional inhibitory concentration (FIC) index was calculated. Results When tested alone, the minimum inhibitory concentration (MIC) values of gentamicin for Gram negative isolates ranged from 8 to > 64 μg/ml. The MIC values of gentamicin for the Gram negative isolates ranged from 1 to 32 μg/ml when tested with Triphala. The FIC index was < 1 indicating a synergistic interaction in 10 of the 11 isolates and it was 1 indicating an additive effect in one isolate. The MIC values of oxacillin for MRSA isolates ranged from 4 to > 16 μg/ml with all MICs being equal to or higher than the resistance cut-off level. The MIC level with the addition of Triphala ranged from 0.25 to 4 μg/ml. FIC index was < 1 for all tested isolates indicating a synergistic interaction. Conclusions Triphala has synergistic activity with gentamicin against the selected MDR Gram negative bacilli and with oxacillin against MRSA isolates warranting further studies on the possibility of clinical use.